KUMMS: optimising DRAM locality with Kernel-user behaviours. (2016) - Sun, Beilei; Li, Xi; Wang, Chao; Wan, Bo; Zhou, Xuehai
DRAM accesses from operating system and user applications are analysed together in the existing researches, which try to improve the DRAM efficiency. In this paper, we find that Kernel and user perform different behaviours while accessing DRAM and interfere with each other greatly. Based on the observations, we divide the DRAM into Kernel-space, user-space and reserved-space. Different policies are designed for different spaces. We also introduce a new lock algorithm for the buddy system to deal with the page requests contentions in the multicore system. Experimental results show that the DRAM locality are averagely improved by more than 10% in the bank:row:column scheme and about 5% in the row:bank:column scheme. The improvements of RBH increase the system throughput without affecting the fairness, and averagely reduce the execution times of different benchmarks by 7.00% and 5.20% in the bank:row:column scheme and row:bank:column scheme, respectively.